2013
DOI: 10.1007/s11255-013-0563-3
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study on the prevalence and incidence of chronic kidney disease in the Netherlands

Abstract: This is the first study to report the incidence rates of all stages of CKD for the entire adult population, stratified by sex, 5-year age groups, and diabetes. Our data demonstrate that the incidence of CKD increases with age and is the highest in participants with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
3
18
3
Order By: Relevance
“…The results revealed that 83.7% of the patients had CKD and none was aware of having the disease. Similar results were found in a retrospective study in Netherlands, where the incidence rate of CKD was highest in participants with diabetes, an incidence of 25 000 per 100 000 person-years (Van Blijderveen et al 2013).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results revealed that 83.7% of the patients had CKD and none was aware of having the disease. Similar results were found in a retrospective study in Netherlands, where the incidence rate of CKD was highest in participants with diabetes, an incidence of 25 000 per 100 000 person-years (Van Blijderveen et al 2013).…”
Section: Introductionsupporting
confidence: 88%
“…Similar results were found in a retrospective study in Netherlands, where the incidence rate of CKD was highest in participants with diabetes, an incidence of 25 000 per 100 000 person‐years (Van Blijderveen et al. ).…”
Section: Introductionsupporting
confidence: 85%
“…In fact, it is well known that the prevalence of diabetes increases significantly with age [41]. The reduction of diabetes in ESRD patients with more than 75 years of age is, probably, explained by the high mortality observed in diabetic ESRD patients, usually due to cardiovascular events [42].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline median duration of diabetes varied from 0 to 29 years. Two studies [29,47] recruited study participants at the time of diabetes diagnosis, but 13 studies did not report the baseline duration of diabetes [12,13,27,36,40,50,56,57,71,74,77,78,81]. Characteristics of the 71 included studies are presented in Table S1.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%